Implikasi Putusan MK No. 102/PUU-VII/2009 Terhadap Pelaksanaan Pemilihan Kepala Daerah (Studi di Kabupaten Malang dan Kota Pasuruan) - Pusat Kajian Konstitusi FH-Universitas Brawijaya (The Constitutional Court of the Republic of Indonesia, 2016)
The Constitutional Court Decision No. 102/PUU-VII/2009 has provided new scope in the implementation of democratization process in Indonesia. The decision has simplyfied the administrative requirement of voters in the Presidential Election held in July 8th 2009, which is the permit to use the Citizen Identification Card (KTP) and Passport as voter identification requirement in voting day. This regulation more or less have strengthen the guarantee of citizen’s rights in this democratic event. The Court decission No. 102/PUU-VII/2009, implicated in building argumentations which related to the Local Election Commision attitudes and policies in resolving problems which occurs in the Fixed List of Voters (DPT) in the event of local elections.